Transition metal carbides (WC, Mo2C, TaC, NbC) as potential electrocatalysts for the hydrogen evolution reaction (HER) at medium temperatures. (23rd February 2015) - Meyer, Simon; Nikiforov, Aleksey V.; Petrushina, Irina M.; Köhler, Klaus; Christensen, Erik; Jensen, Jens Oluf; Bjerrum, Niels J.
Abstract: One limitation for large scale water electrolysis is the high price of the Pt cathode catalyst. Transition metal carbides, which are considered as some of the most promising non-Pt catalysts, are less active than Pt at room temperature. The present work demonstrates that the situation is different at medium temperatures (200–400 °C). By introducing a new setup which makes use of molten KH2 PO4 as electrolyte, a model system for solid acid membrane electrolyser cells was obtained. Metal carbide coated wires prepared by a two-step oxidation–carburization reaction of the metal wire surfaces were used as electrodes and allowed the measurement of the intrinsic catalytic properties of different transition metal carbides in direct comparison to Pt at 260 °C. Under these conditions, the activity in the hydrogen evolution reaction (HER) followed the order WC > Pt ≈ Mo2 C > NbC > TaC.